Pemanfaatan Kompos Bagase Tebu dan Efektifitas Penggunaan Pupuk N terhadap Pertumbuhan Vegetatif Kakao (Theobroma cacao L.) - Muhammad Firmansayah; Erfan Wahyudi; Irwan Agusnu Putra; Dedi Kurniawan (Prodi. Agroteknologi dan Perkebunan, Universitas Tjut Nyak Dhien, 2020)
Introduction: This research was determined the growth response of cocoa (Theobroma cacao L.) in N-fertilizer and sugarcane bagasse compost. Materials and Methods: This research was conducted at agricultural area of ​​Sejati Street, Sari Rejo Village, Medan Polonia Sub-District, Medan. This research was conducted from August until December 2015. This research used therandomized block design in factorial. The first factor was N-fertilizer with 4 rates, 0 g.polybag-1 (P0), 2 g.polybag-1 (P1), 4 g.polybag-1 (P2),and 6 g.polybag-1 (P3). The second factor was the provision of sugarcane bagasse compost with 4 rates, 0 g.polybag-1 (K0), 2 g.polybag-1 (K1), 4 g.polybag-1 (K2) and 6 g.polybag-1 (K3). The observed data were analyzed by the F-test, and continued with the DMRT at level of 5%. Results: Composting bagase significantly affected the leaf area of cocoa seedling at 2 and 4 weeks after planting. The application of N-fertilizer had significant affected the number of leaves for cocoa seedling. The interaction of P2K2 (6 g.polybag-1 N and 4 g.polybag-1 of bagasse compost) showed the highest fresh- and dry-weight of cocoa seedling compared to other interactions, although the effect was not significant.